Future Solvency Prediction for Property Insurance Companies - Le, Min; Xu, Jingfeng (Advances in Social Sciences Research Journal, 2019)
The service period of insurance products is often a period of time after purchasing products. Therefore, using the existing information to assess the future solvency of the insurance company is very important to the policyholders’ insurance purchase decision and equivalently important to the operation of the insurance companies. Our research sets up a model to predict the solvency of the property insurance companies in the coming year, focusing on whether the two indexes of the company size and the current solvency adequacy ratio are strong and reliable, and to provide support for policyholders’ insurance purchase decisions. We show that, contrary to the conventional thought that big companies are more solvent, company size has a negative impact on its future solvency. And the current solvency adequacy ratio is a reliable index to predict the future solvency so that our research results also indicate the regulatory supervision of solvency is beneficial to take action to protect the interests of the policyholders as soon as possible.